2000
DOI: 10.1074/jbc.275.2.1023
|View full text |Cite
|
Sign up to set email alerts
|

Nramp2 Expression Is Associated with pH-dependent Iron Uptake across the Apical Membrane of Human Intestinal Caco-2 Cells

Abstract: The absorption of dietary non-heme iron by intestinal enterocytes is crucial to the maintenance of body iron homeostasis. This process must be tightly regulated since there are no distinct mechanisms for the excretion of excess iron from the body. An insight into the cellular mechanisms has recently been provided by expression cloning of a divalent cation transporter (DCT1) from rat duodenum and positional cloning of its human homologue, Nramp2. Here we demonstrate that Nramp2 is expressed in the apical membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
182
3
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(200 citation statements)
references
References 25 publications
13
182
3
2
Order By: Relevance
“…This suggests a higher expression of DMT1 within certain areas of the basal ganglia, which may explain the sensitivity of this region to Mn toxicity and the overlap in motor deficits observed in patients suffering from PD and manganism. In rats, DMT1 expression is highest in astrocytes and endothelial cells within the striatum, granule and Purkinje cells of the cerebellum, in neurons within the thalamus and in ependymal cells lining the third ventricle (Burdo et al, 2001;Tandy et al, 2000), with moderate staining in the substantia nigra (Gunshin et al, 1997).Based on the existing knowledge on the localization of DMT1, the proposed pathway for Mn uptake by the gastrointestinal tract and its transport into the blood stream and across the BBB is depicted in Figure 3. …”
mentioning
confidence: 99%
“…This suggests a higher expression of DMT1 within certain areas of the basal ganglia, which may explain the sensitivity of this region to Mn toxicity and the overlap in motor deficits observed in patients suffering from PD and manganism. In rats, DMT1 expression is highest in astrocytes and endothelial cells within the striatum, granule and Purkinje cells of the cerebellum, in neurons within the thalamus and in ependymal cells lining the third ventricle (Burdo et al, 2001;Tandy et al, 2000), with moderate staining in the substantia nigra (Gunshin et al, 1997).Based on the existing knowledge on the localization of DMT1, the proposed pathway for Mn uptake by the gastrointestinal tract and its transport into the blood stream and across the BBB is depicted in Figure 3. …”
mentioning
confidence: 99%
“…Hence, the transport of iron generates a positive inward current (12,26,29). The finding that DMT1-expressing oocytes also generate positive inward currents when exposed to Zn 2ϩ , Cd 2ϩ , Mn 2ϩ , Cu 2ϩ , Fe 2ϩ , Co 2ϩ , Ni 2ϩ , and Pb 2ϩ raised the possibility that these cations could also be transported by DMT1.…”
mentioning
confidence: 99%
“…Moreover, Mn 2ϩ uptake is severely diminished when the cells express DMT1 with the mk mutation (4,9). In contrast, 65 Zn 2ϩ uptake into Caco-2 cells is not affected by cell iron status or by dissipation of the membrane potential, and it is not dependent on an acidic extracellular pH (29). Moreover, in the oocyte expression system, Zn 2ϩ elicits an inward proton flow that is not accompanied by actual metal transport (26).…”
mentioning
confidence: 99%
“…The expression of DMT1 in the small intestine is negatively regulated by iron status (Tandy et al, 2000;Trinder et al, 2000;Yeh et al, 2000;Gunshin et al, 2001). However, DMT1 expression in hepatocytes is positively regulated by iron at the posttranscriptional level (Trinder et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have shown that DMT1 might play an important role in iron transport across the apical surface of intestinal enterocytes (Tandy et al, 2000;Trinder et al, 2000), and that it might be involved in translocation of iron from endosome to cytosol under physiological conditions Gruenheid et al, 1999;Tabuchi et al, 2000). It was reported that DMT1 might have a role in Tf-dependent iron uptake in some types of cells (Wardrop and Richardson, 1999).…”
Section: Discussionmentioning
confidence: 99%